2016
DOI: 10.1155/2016/6978923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TRPV4-p38 MAPK Pathway on Neuropathic Pain in Rats with Chronic Compression of the Dorsal Root Ganglion

Abstract: The aim of this study was to investigate the relationships among TRPV4, p38, and neuropathic pain in a rat model of chronic compression of the dorsal root ganglion. Mechanical allodynia appeared after CCD surgery, enhanced via the intrathecal injection of 4α-phorbol 12,13-didecanoate (4α-PDD, an agonist of TRPV4) and anisomycin (an agonist of p38), but was suppressed by Ruthenium Red (RR, an inhibitor of TRPV4) and SB203580 (an inhibitor of p38). The protein expressions of p38 and P-p38 were upregulated by 4α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…After various stress stimuli, p38 is phosphorylated in association with sequential activation of MAPK kinase kinase and MAPK kinase 6 cascades [9]. This pp38 is involved in producing various downstream intracellular molecules in DRG neurons [21]. The present fi ndings showed a signifi cant increase in the number of pp38-IR cells in the TG in dry-tongue rats and considerable suppression of the number of pp38-IR cells after continuous intraganglionic administration of p38 MAPK inhibitor in these animals.…”
Section: Discussionsupporting
confidence: 53%
“…After various stress stimuli, p38 is phosphorylated in association with sequential activation of MAPK kinase kinase and MAPK kinase 6 cascades [9]. This pp38 is involved in producing various downstream intracellular molecules in DRG neurons [21]. The present fi ndings showed a signifi cant increase in the number of pp38-IR cells in the TG in dry-tongue rats and considerable suppression of the number of pp38-IR cells after continuous intraganglionic administration of p38 MAPK inhibitor in these animals.…”
Section: Discussionsupporting
confidence: 53%
“…It has been identified that an ERK1/2 inhibitor decreased the expression of Piezo1 in neonatal rat ventricular myocytes, whereas this effect was not observed when p38 and JNK inhibitors were applied (21). Additionally, the p38 inhibitor SB203580 enhanced the expression of TrPV4 in the dorsal root ganglion (22). collectively, these observations suggest that MaPKs may participate in signal transduction pathways downstream of MScs under conditions of mechanical loading.…”
Section: The Roles Of Mechanosensitive Ion Channels and Associated Domentioning
confidence: 65%
“…Changes in the level of nitrite are positively associated with the changes in thermal hyperalgesia. Identified signaling pathways involved in the CCD neuropathic pain model include NF-kappa-B, which mediates the TRPV4-NO pathway [288] and the p38 pathway [289].…”
Section: Trpv4 In Transduction Of Mechanically-evokedmentioning
confidence: 99%